Towards a strontium optical lattice clock - Bridge, E; Elizabeth Michelle Bridge (2012)
Due to the recent success, in terms of accuracy and precision, of a number of strontium optical lattice optical frequency standards, and the classification of the 5s2 1S0 to 5s5p 3P0 transition in neutral strontium as a secondary definition of the SI unit of the second, many new strontium lattice clocks are under development. The strontium optical lattice clock (Sr OLC) at the National Physical Laboratory (NPL) is one such project. This thesis describes the design and build of the NPL Sr OLC, discussing the considerations behind the design. Details of the first cooling stage are given, which includes the characterisation of a novel permanent-magnet Zeeman slower by measurements of the longitudinal velocity distributions and loading of the MOT at 461 nm. Development of a narrow linewidth laser system at 689 nm is described, which is used for initial spectroscopy of the second-stage cooling transition. In particular, this work describes progress towards two independent ultra-narrow linewidth clock lasers. The new generation of strontium lattice clock experiments have focused on characterising the systematic frequency shifts and reducing their associated fractional frequency uncertainties, as well as reducing the fractional frequency instability of the measurement. One focus of the Sr OLC at NPL is to help characterise the frequency shift of the clock transition due to black-body radiation (BBR), which is currently the largest contributor to the uncertainty budget of the measured clock frequency. Our approach, discussed here, is to make a direct, differential measurement of the shift with the atoms housed alternately in environments of differing temperatures. Better characterisation and control of the BBR frequency shift of the strontium clock transition is crucial for the future of the Sr OLC as a leading frequency standard.